Automated multi‐sample DNA extraction for genotyping live Xenopus embryos. Issue 3 (19th October 2022) - Alles, Narmadha; Guille, Matthew; Górecki, Dariusz C.
Abstract: Background: Xenopus frogs are used extensively for modeling genetic diseases owing to characteristics such as the abundance of eggs combined with their large size, allowing easy manipulation, and rapid external embryo development enabling the examination of cellular and phenotypic alterations throughout embryogenesis. However, genotyping of mutant animals is currently done either as part of a large group, requiring many embryos, or late in development with welfare effects. Therefore, we adapted the Zebrafish Embryonic Genotyper for rapid genomic DNA extraction from Xenopus tropicalis and Xenopus laevis at early stages. Results: Sufficient and good quality DNA was extracted as early as the Nieuwkoop and Faber stage 19 and, importantly, no detrimental effects of the extraction process on the subsequent tadpole development, behavior, or morphology were observed. Amplicons of up to 800 bp were successfully amplified and used for further analyses such as gel electrophoresis, T7 endonuclease I assay and Sanger sequencing. Conclusion: This method allows rapid genotyping during the early stages of Xenopus development, which enables safe identification of mutants. These can be analyzed at early developmental stages or selected for raising without the need for invasive genotyping later, with resource savings and ethical gains in line with the 3Rs principles. Key Findings: Xenopus frogs are used extensively for modelling genetic diseases. However, current procedures for genotyping of mutant animals require many embryos, or are done late in development, which hampers experiments have welfare effects. Therefore, we developed a method allowing rapid genotyping during the early stages of Xenopus development, which has no detrimental effects on the subsequent tadpole growth, with resource savings and ethical gains in line with the 3Rs principles.